2020
DOI: 10.21037/med-20-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different sedation modalities on endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA)

Abstract: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is an important tool in diagnosis and staging of lung and mediastinal disease. However, opinions regarding patient sedation are controversial. Moderate sedation, deep sedation and general anesthesia are widely used with different criteria by many centers. The choice of sedation varies also depending on the type of operator performing the EBUS-TBNA and the location. The operator can be either a thoracic surgeon or a pulmonologist. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It has been reported that desaturations during bronchoscopy are temporary and do not require any special treatment other than oxygen support. [18] This study has several limitations. We had to rely on patient records for intraoperative hemodynamic data, sedation scores, and side effects.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that desaturations during bronchoscopy are temporary and do not require any special treatment other than oxygen support. [18] This study has several limitations. We had to rely on patient records for intraoperative hemodynamic data, sedation scores, and side effects.…”
Section: Discussionmentioning
confidence: 92%
“…As endoscopic ultrasound procedures become more widely employed around the world, there is an increased interest in the most ideal modality for periprocedural sedation. It is a balance between resource availability, cost consideration, bronchoscopist preference, patients’ comfort, and diagnostic yield [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the process is generally lengthy, unpleasant, and extremely irritating to the airway, it is preferably conducted under sedation [ 3 , 4 ]. Previous research has indicated that deep sedation increases diagnostic yield and the amount of lymph nodes examined compared to moderate sedation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%